Engineering mechanics : dynamics - Hibbeler, R. C. (Always learning., 2017)
For Dynamics Courses. A Proven Approach to Conceptual Understanding and Problem-solving Skills Engineering Mechanics: Dynamics excels in providing a clear and thorough presentation of the theory and application of engineering mechanics. Engineering Mechanics empowers students to succeed by drawing upon Prof. Hibbeler's everyday classroom experience and his knowledge of how students learn. This text is shaped by the comments and suggestions of hundreds of reviewers in the teaching profession, as well as many of the author's students. The Fourteenth Edition includes new Preliminary Problems